Are private banks the better banks? An insight into the principal-agent structure and risk-taking behavior of German banks - Frank Schmielewski; Thomas Wein (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
In this study, we propose our hypothesis that the distinguishable principal-agent relationships of German banks are significantly influencing the risk-taking attitudes of bank managers. Particularly, we intend to substantiate the theory that banks owned by dispersed shareholders or federal state authorities face a higher relevance of principal-agent problems than other banking sectors due to a missing ability to monitor bank managers. Our results underline that these problems appear to mislead bank managers showing an unreasonable risk-taking behavior. In a first stage, we rely on a theoretical model explaining that from the bank owners' viewpoint three factors of the principal-agent relationships are determining the probability of choosing the optimal portfolio of risky assets. These factors cover the ability to control bank managers, the risk pooling capabilities of bank owners and bank managers, and the incentives of seeking high returns. To support our hypothesis we apply an empirical study to the distances-to-default of different German banking sectors. This demonstrates that risktaking attitudes of banks are closely related to banks' ownership. Consequently, our findings offer evidence, that legislative and regulatory authorities should increase their vigilance in terms of principal-agent problems within certain sectors of the banking industry.
Keywords: G01; G12; G14; G28; G15; G32; 330; financial crises; risk-taking behavior; risk aversion; efficient portfolios; information asymmetries and market efficiency; government policy and regulation; risk pooling; seeking for high returns; monitoring capabilities; capital and ownership structure; distance-to-default; capital asset ratio; return on assets